Improving access to birth attention of marginalized populations in Peru - Seinfeld, Janice (2011)
In the last 15 years, maternal mortality rates have been significantly reduced in Peru. In 1996, this rate was as high as 31.6 per 100,000 women while in 2009 it was reduced to 8.5 per 100,000 women. These improvements, although significant, were neither enough Peru is still well behind developed countries rates? nor solved inequality problems across different groups and areas, especially for poor women living in the Selva region and in rural areas. Strategies to reduce economic, accessibility and cultural barriers are necessary to increase institutional deliveries? rate, and thus reduce maternal mortality. Although information on maternal mortality is scarce, we rely on the strong correlation between this variable and institutional delivery in Peru to analyze the factors contributing to maternal mortality. Internationally, institutional delivery has been found as good predictor of maternal mortality by several authors.